Guarding the “Helsinki Spirit”: Yugoslavia and the CSCE Continuity (1975–1976) - ČAVOŠKI, Jovan (CURRENTS OF HISTORY, 2026)
This article deals with the diplomatic efforts that marked the period after the introduction of the Helsinki Final Act, observed not only from the viewpoint of socialist Yugoslavia as the host of the future CSCE Belgrade Follow-up Meeting, but also from the standpoint of the complex relationships existing in Europe between the two blocs during the years in question. Particular attention is devoted to the ties between Yugoslavia and the group of neutral and non-aligned countries, which jointly gave a considerable contribution to the concept of CSCE continuity. This article is primarily based on documents from Serbian and U.S. archives.Summary: The introduction of the Helsinki Final Act in August of 1975 represented a defining political moment in the recent history of Europe, when the territorial and political status-quo inherited after the end of the Second World War was legally accepted by all interested parties – Eastern Bloc, Western Bloc, and N+N. This important document was the final outcome of three years of complex negotiations between all these factors at the CSCE, while its provisions, presented in three "baskets" dealing with political, economic, and humanitarian issues, stipulated the existing political structure on the continent. However, as soon as the Helsinki summit ended, the interest of bloc factors in promoting the CSCE’s full implementation and continuity had started to wane or it was only motivated by a pragmatic dedication to certain areas that could prove to be of some political use for both blocs (human rights for the West, economic and technological cooperation for the East). Therefore, in the aftermath of the Helsinki summit, Yugoslavia was compelled to launch a new round of intensive dialogue with both blocs, which was supposed to reignite their interest in the CSCE process, thus enlisting their constructive, though limited support for the forthcoming Belgrade Follow-up Meeting. In this enterprise, Belgrade also succeeded in gaining the strong backing of the N+N group, while also avoiding taking sides with any of the superpowers, which finally enabled all participants to initiate preparations for the new round of CSCE negotiations in the Yugoslav capital.